STRATEGI PEMASARAN MENGGUNAKAN STORYTELLING CERITA LEGENDA PADA SITUS TOBA KALDERA: PUSUK BUHIT SEBAGAI TEMPAT AWAL MUASAL SUKU BATAK - Posma Sariguna Johnson Kennedy1,; Suzanna Josephine Tobing 2; Lumbantoruan 3, Rutman; Ricky Martin Manullang 4 (Universitas Kristen Indonesia, 2023)
This paper describes the importance of storytelling as an effective marketing strategy for tourism promotion. A captivating story can make a tourist destination come alive and attract visitors to learn more about it. Additionally, local wisdom and legends, part of a culture's heritage, should be preserved and used to promote tourism. Specifically, this paper explores the narratives and legends of Pusuk Buhit, a destination in the Toba Caldera UNESCO Global Geopark in Samosir, North Sumatra, Indonesia. The qualitative method is used to interpret the data collected from the field. The study highlights the importance of preserving local wisdom and legends to promote tourism and preserve cultural heritage. Keywords: Marketing Strategy, Storytelling, Toba Caldera, Pusuk Buhit, Batak Tribe